2015
DOI: 10.1017/thg.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment Among Singletons and Multiple Births in Japan: A Population-Based Study

Abstract: Background: The occurrence of multiple births has been recognized as a risk factor for child maltreatment. However, few population-based studies have examined the relationship between multiple births and child maltreatment. This study aimed to evaluate the degree of risk of child maltreatment among singletons and multiple births in Japan and to identify factors associated with increased risk. Methods: Using population-based data, we analyzed the database of records on child maltreatment and medical checkups fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Meanwhile, according to a population-based study, the risk of child maltreatment is higher in multiple births. However, findings from our study showed that multiple birth was not associated with increased risk of child maltreatment (Yokoyama et al, 2015). Compared with singletons, multiples had a significantly higher rate of risk factors for child maltreatment including low birth weight, disorders of the nervous system, and poor maternal health.…”
Section: Focus Of the Studycontrasting
confidence: 71%
“…Meanwhile, according to a population-based study, the risk of child maltreatment is higher in multiple births. However, findings from our study showed that multiple birth was not associated with increased risk of child maltreatment (Yokoyama et al, 2015). Compared with singletons, multiples had a significantly higher rate of risk factors for child maltreatment including low birth weight, disorders of the nervous system, and poor maternal health.…”
Section: Focus Of the Studycontrasting
confidence: 71%
“…The magnitude of the simultaneous parental investment is larger for parents of twins compared to parents of age-discrepant siblings. This could increase, for example, parental stress (Thorpe et al, 1991), which might constitute risk factors for child victimization (Yokoyama et al, 2015). Lastly, although the current sample is highly representative of the Finnish population (Johansson et al, 2013; Rehan et al, 2017), some cultural aspects pertinent to child victimization might not generalize to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded twin birth samples (n = 110; the proportion of the whole sample was 1.7%) as they increase the risk of perception of infant crying [21], mother-infant interaction [32], and abusive behavior [33][34][35], and causes the ambiguity of which out of the infertility treatment and the twin was investigated. We also excluded samples with missing values for infertility treatment history, perception of infant crying, bonding impairment, abusive behavior, and parental age, as parental age is a strong predictor of infertility treatment [36,37] (n = 90, 1.4% of the respondent sample).…”
Section: Procedures and Participantsmentioning
confidence: 99%